Density Functional Theory Studies of MXene-Based Nanosensors for Detecting Volatile Organic Compounds in Meat Spoilage Assessment - Hakkim Vovusha; Hyeonhu Bae; Seunghan Lee; Jusang Park; Ali Raza; Komsilp Kotmool; Tanveer Hussain; Hoonkyung Lee (ACS Applied Nano Materials, 2023)
Emission of selected volatile organic compounds (VOCs), such as methylamine (MA), dimethylamine (DMA), and trimethylamine (TMA), is associated with certain microbial reactions, causing intrinsic decomposition and spoilage of meat and fish. Efficient detection of MA, DMA, and TMA is vital for meat and fish spoilage assessment. Here, density functional theory (DFT) calculations are used to study the sensing properties of selected MXene monolayers (M2CTx; M = Ti, Nb, V; Tx = O, OH, F) toward MA, DMA, and TMA. We found that the binding energies of MA (−0.29 to −1.08 eV), DMA (−0.39 to −1.15 eV), and TMA (−0.28 to −1.19 eV) on M2CTx are ideal for reversible sensing. Appropriate binding of these VOCs is associated with measurable changes in the electronic properties of M2CTx, which is essential for a highly efficient sensing mechanism. Further, we used the Langmuir adsorption model to explore the sensing characteristics of M2CTx monolayers in varied temperature and pressure environments. Among the studied systems, Nb2C(OH)2 exhibits excellent sensing capabilities toward DMA and TMA at concentrations below parts per million (ppm), whereas Nb2CF2 exhibits selective adsorption of MA at concentrations below ppm. We strongly believe that our findings will pave the way for the development of highly sensitive nanosensors for monitoring the spoilage of meat and fish products.
Keywords: MXene and MAX Phase Materials; 2D Materials and Applications; Advanced biosensing and bioanalysis techniques